Peningkatan Kinerja Tenaga Kerja Bagian Sortasi Dan Grading Kulit Kayu Manis (C. Burmanii) Pada Cv. Rasdi & Co Berdasarkan Faktor-Faktor Yang Berpengaruh - Andri Syaputra (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2019)
Labour productivity is also greatly influenced by working procedures, the skills of workers, machine design and production equipment, as well as working environment. In this research, doing the identification of factors affecting the workers in sorting and grading of cinnamon skin department. The five factors are used as independent variables were the work motivation (X1), work environment (X2), salary (X3), age (X4) and workload (X5) that are correlated with one dependent variable which is the performance (Y). The Research conducted at Rasdi Fo & Co Jl. Adinegoro No. 38. 25172 Padang Lalang Simpang West Sumatra. Sampling extraction  method used in this study was stratified random sampling method. The Respondents were ≥ 25% from 70 production employees of Rasdi Fo & Co. and the characteristic features are based on years of service, so the method that would be used was to look at the curriculum vitae of employees and then grouped based on the length of working as the representative of the entire population. The measurement results obtained, the results of the maximum temperature was 38,44 °C and a minimum temperature was 29.33 °C and this did not meet the standards set. The results of a maximum humidity was 91.3% and minimum humidity was 59,2 % and also did not meet the standards set. The highest noise level was 78,4 dBA and at the lowest measurement was 48,8 dBA and was classified as normal without ear protection (1405/MENKES/SK/XI/ 2002).